Extracción de pectina del exocarpo y endocarpo de la pitahaya (Hylocereus triangularis) para uso agroindustrial. - Muñoz Quintana, María Elizabeth (2014)
This research aimed to extract pectin from endocarp and exocarp of pitahaya and make better use of existing raw material and get a good quality product. The pectin extraction process was conducted in the laboratories of the School of Chemical Engineering Agroindustrial the corresponding laboratories in purpose of the Faculty of Engineering in Agricultural Sciences at the State Technical University of Quevedo analysis. Applying three factors with two levels . Maturity, green and ripe fruit Part ; endocarp and exocarp , and type of acid , hydrochloric , sulfuric and nitric ……